Case series: Intraoperative neuromonitoring and angiography in the surgical treatment of vascular malformations - Šmigoc, Tomaž; Kozorog, Ninna; Ravnik, Janez (Frontiers in Neurology, 2023)
In the surgical treatment of cerebral vascular malformations, e.g., aneurysms and arteriovenous malformations, the risk of ischemic complications is 6.7%, and a residual aneurysm is possible in 5.2% of these cases. Ischemic lesions can result in permanent neurological deficits, and a residual aneurysm can lead to the recurrence of the aneurysm in 2% of cases. In this article, we present five cases (two cases of ruptured aneurysms, two cases of non-ruptured aneurysms, and a case of arteriovenous malformation) in which we reduced the aforementioned risks with the use of intraoperative neuromonitoring and angiography. Intraoperative neuromonitoring (IONM) is used to measure motor and sensory-evoked potentials to detect brain hypoperfusion. Intraoperative angiography with the dye indocyanine green (ICG-A), which fluoresces in a vessel under a microscope after intravenous administration, helps to identify residual aneurysm sacs and distal blood flow. With the use of IONM and ICG-A, we identified abnormalities and adjusted our interventions and treatments. IONM and ICG-A can lead to a better outcome after surgical treatment of cerebral vascular abnormalities.